Unidad didáctica para fortalecer el desarrollo del pensamiento espacial en estudiantes de grado sexto: las joyas de platón y la papiroflexia (2018)
This document deploys a proposal to strengthen spatial thinking in sixth grade students, having as a legal framework the General Education Law 115, as well as the Guidelines, Standards and Basic Learning Rights, which establish the development of spatial thinking in the grade. sixth. Understanding that the construction of this thinking in the classroom traditionally occurs from the perspective of the two-dimensional in a three-dimensional world, it is evident that students have some shortcomings when working with different solids, which is why this monographic work is proposed, from the background analysis, where a consultation is made of some local, national and international works that refer to the teaching of solids and spatial thinking with tangible manipulative material; For the design of the proposal it was necessary to understand the Platonic solids and their characteristics, as well as the creation of a pedagogical framework that is based on meaningful learning